2014
DOI: 10.1002/jwmg.707
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Atlantic Flyway resident population Canada geese in New Jersey

Abstract: Atlantic Flyway Resident Population Canada geese (Branta canadensis) are long-lived birds that were established during the mid-1900s. At high densities, resident Canada geese reduce water quality, impair landscape aesthetic, damage crops, and cause safety concerns. Managers need information about survival to more effectively manage these populations via implementation of harvest and cull regulations. We analyzed records for 39,711 Canada geese captured 54,309 times during 1994-2011, of which 5,883 were recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 26 publications
3
20
1
Order By: Relevance
“…We found that survival of both adult rural and adult urban geese was greater during mild winters than during severe and moderate winters. Adult survival was comparable to other published survival rates (0.65) for temperate breeding geese in mid-latitude states (Lawrence et al 1998) and somewhat lower than published survival rates for Atlantic Flyway temperate breeding populations (0.828, 0.718-0.724, and 0.717-0.810, Johnson and Castelli 1998, Beston et al 2014, Conover et al 2015. Even though urban-rural status was an important predictor variable in the highest-ranked model, we found a smaller difference in survival when comparing survival of urban and rural cohorts of geese in Ohio compared with other published studies (Balkcom 2010, Beston et al 2014.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that survival of both adult rural and adult urban geese was greater during mild winters than during severe and moderate winters. Adult survival was comparable to other published survival rates (0.65) for temperate breeding geese in mid-latitude states (Lawrence et al 1998) and somewhat lower than published survival rates for Atlantic Flyway temperate breeding populations (0.828, 0.718-0.724, and 0.717-0.810, Johnson and Castelli 1998, Beston et al 2014, Conover et al 2015. Even though urban-rural status was an important predictor variable in the highest-ranked model, we found a smaller difference in survival when comparing survival of urban and rural cohorts of geese in Ohio compared with other published studies (Balkcom 2010, Beston et al 2014.…”
Section: Discussionsupporting
confidence: 82%
“…Adult survival was comparable to other published survival rates (0.65) for temperate breeding geese in mid-latitude states (Lawrence et al 1998) and somewhat lower than published survival rates for Atlantic Flyway temperate breeding populations (0.828, 0.718-0.724, and 0.717-0.810, Johnson and Castelli 1998, Beston et al 2014, Conover et al 2015. Even though urban-rural status was an important predictor variable in the highest-ranked model, we found a smaller difference in survival when comparing survival of urban and rural cohorts of geese in Ohio compared with other published studies (Balkcom 2010, Beston et al 2014. This may be a limitation of how urban and rural status was designated (i.e., post hoc Geographic Information System analysis as compared with other studies where urban or rural status was identified at the time of banding) or there might only be slight differences between urban and rural goose survival at the state level in Ohio.…”
Section: Discussionsupporting
confidence: 82%
“…In 56 state–year combinations, juvenile survival was higher than adult survival; whereas, the remaining 48 state–year combinations showed no difference. Previous studies of migratory Canada geese found that juveniles had lower survival than adults (Pollock 1981, Samuel et al 1990), whereas resident Canada geese had higher survival for juveniles in some areas (Groepper et al , Beston et al ). One potential reason that juvenile Canada geese from resident populations may fare better than those from subarctic‐nesting populations is that resident population geese migrate only short distances, if at all, and thus experience reduced migration costs.…”
Section: Discussionmentioning
confidence: 94%
“…Our estimates of annual survival of Resident geese are similar to previous estimates from states within the Atlantic Flyway and from other temperate‐breeding Canada goose populations. Adult geese in New Jersey had a survival rate of approximately 0.72 (1994–2011; Beston et al ), and Resident geese at a rural study site in Georgia had an annual survival rate of 0.682 (2001–2006; Balkcom ). Survival of locally nesting adult geese in southern Ontario (1989–2009) ranged from 0.57 to 0.90 (Iverson et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation